Electric Field Based Dressing Disrupts Mixed-Species Bacterial Biofilm Infection and Restores Functional Wound Healing. Issue 4 (April 2019) - Barki, Kasturi Ganesh; Das, Amitava; Dixith, Sriteja; Ghatak, Piya Das; Mathew-Steiner, Shomita; Schwab, Elizabeth; Khanna, Savita; Wozniak, Daniel J.; Roy, Sashwati; Sen, Chandan K.
Abstract : Objective: This study was designed to employ electroceutical principles, as an alternative to pharmacological intervention, to manage wound biofilm infection. Mechanism of action of a United States Food and Drug Administration-cleared wireless electroceutical dressing (WED) was tested in an established porcine chronic wound polymicrobial biofilm infection model involving inoculation with Pseudomonas aeruginosa PAO1 and Acinetobacter baumannii 19606. Background: Bacterial biofilms represent a major wound complication. Resistance of biofilm toward pharmacologic interventions calls for alternative therapeutic strategies. Weak electric field has anti-biofilm properties. We have previously reported the development of WED involving patterned deposition of Ag and Zn on fabric. When moistened, WED generates a weak electric field without any external power supply and can be used as any other disposable dressing. Methods: WED dressing was applied within 2 hours of wound infection to test its ability to prevent biofilm formation. Alternatively, WED was applied after 7 days of infection to study disruption of established biofilm. Wounds were treated with placebo dressing or WED twice a week for 56 days. Results: Scanning electron microscopy demonstrated that WED prevented and disrupted wound biofilm aggregates. WED accelerated functional wound closure by restoring skin barrier function. WED blunted biofilm-induced expression of (1) P. aeruginosa quorum sensing mvfR (pqsR), rhlR and lasR genes, and (2) miR-9 and silencing of E-cadherin. E-cadherin is critically required for skin barrier function. Furthermore, WED rescued against biofilm-induced persistent inflammation by circumventing nuclear factor kappa B activation and its downstream cytokine responses. Conclusion: This is the first pre-clinical porcine mechanistic study to recognize the potential of electroceuticals as an effective platform technology to combat wound biofilm infection. Abstract : Supplemental Digital Content is available in the text